Of Pastorals and Partisans: Nationalist Variations on the Myth of Rural Virtue in Sixteenth-Century Anti-Protestant Polemics - Flood, Christopher M. (The sixteenth century journal, 2020)
In the tumultuous time preceding the French Wars of Religion, one innovative partisan author infused his anti-Protestant rhetoric with nationalistic discourse based in the myth of rural virtue. Drawing on existing anxieties regarding urbanization, Artus Désiré depicted Geneva as a festering slum teeming with corruption and debauchery. He contrasted this with an idyllic French countryside inhabited by traditional, rustic characters whose innocence fostered pure devotion and protected them from Calvinism's corrupting influence. Building on this dichotomy, Désiré conflated socioeconomic divisions with political borders and theological distinctions to further alienate Calvin and his followers. In his portrayal, Calvinists had abandoned their native communities in favor of a foreign heresy associated with the corrupt and corrupting urban landscape. By recontextualizing the immediate conflict, Désiré provided a model for future anti-Protestant polemics.